The impact of education reforms on development of continuing vocational education in Turkey - Malyshevа, Machyrа (Professional Pedagogics, 2018)
The article analyzes modern education reforms in Turkey and justifies their impact on development of continuing vocational education in the country. It was found that the reforming of vocational education and training in Turkey is carried out by the Ministry of National Education. It was stated that the system of vocational education in Turkey is aimed at performing innovative functions in the specialists’ vocational training, since their relevance is confirmed by the experience of developed countries and the European Union. However, the strategies for continuing education development in Turkey complement formal, non-formal and informal education to create a flexible system of lifelong learning.It was determined that core elements in reforming vocational education include establishing the links between the system of vocational education and the labour market; developing vocational standards and prospective training standards; designing vocational education curricula taking into account competency- and module-based approaches and learning outcomes; strengthening social partnership in vocational education; justifying and implementing the concept of lifelong learning etc. It was indicated that the lifelong learning concept implementation required that Turkish government develop and approve legislative and regulatory documents (the Law on Vocational Qualification Authority; the Non-Formal Education Institutions Decree etc.), aimed at realizing core principles of a Memorandum on Lifelong Learning in Europe.It was concluded that the above-mentioned reforms related to the lifelong learning concept implementation in Turkey are extremely important for the country’s innovative progress in the European area.
Keywords: education reforms; Turkey; vocational education and training; continuing vocational education; lifelong learning